Correlates of Current Smoking Among Adults Served by the Public Mental Health System. Issue 2 (3rd April 2017) - Swarbrick, Margaret A.; Cook, Judith A.; Razzano, Lisa A.; Jonikas, Jessica A.; Gao, Ni; Williams, Jill; Yudof, Jay
ABSTRACT: Objective: As part of a study of health status among 457 adults with diagnostically heterogeneous serious mental illnesses served by the public mental health system in four U.S. states, we assessed predictors of current cigarette smoking.Methods: We examined bivariate relationships between smoking status and risks for drug and alcohol use disorders, residential setting, parental status, and employment. Finally, we used multivariable logistic regression to predict current smoking, controlling for significant confounds.Results: Of the total sample, 44% of participants reported that they currently smoked and most (62%) were moderately to severely nicotine-dependent. Those at high risk for drug use disorders were more than three times as likely and those at high risk for alcohol use disorders were more than twice as likely to smoke, compared to their counterparts with little or no drug or alcohol use disorder risk. Controlling for all other model variables including drug and alcohol disorder risk, current smokers were less likely to be parents and more likely to reside in supervised settings than nonsmokers. Younger people and those without a college degree were more likely to smoke, controlling for all other model variables.Conclusions: Given the high degree of comorbidity of smoking, alcohol disorders, and drug use disorders, the authors highlight the need for integrated interventions that address these issues simultaneously.